Legend of the lost legend - Stine, R. L. (New York : Scholastic, 1996)
Justin and Marissa want to help their dad search for an ancient manuscript. However, they get lost in the woods of Brovania. The woods are filled with very strange creatures ...
440
440
Accelerated Reader AR
Keywords: Horror fiction